The predictive value of pretreatment haemoglobin-to-red cell distribution width ratio for overall survival of patients with advanced non-small cell lung cancer: a propensity score matching analysis. Issue 4 (April 2021) - Jiang*, Huiqin; Jiang*, Wei; Tan, Liping; Yu, Qitao; Liu, Feiwen; Huang, Yucong; He, Jianbo; Zhou, Shaozhang
Objective: To investigate the prognostic value of pretreatment haemoglobin-to-red cell distribution width radio (HRR) in predicting overall survival (OS) in patients with advanced non-small cell lung cancer (NSCLC). Methods: This retrospective study analysed patients with advanced NSCLC. Kaplan–Meier survival analysis and Cox proportional hazards regression analysis were conducted to evaluate the predictive value of HRR for OS. A propensity matching analysis was used to reduce the impact of other confounding factors on the results. Results: A total of 448 patients were enrolled in the study. The median HRR was 0.984, which was used as the cut-off value. Regardless of matching or not, a lower HRR was correlated with an unfavourable risk of death. After propensity matching, univariate and multivariate analysis showed that HRR was an independent factor for the prognosis of NSCLC (hazard ratio [HR] 1.55, 95% confidence interval [CI] 1.17, 2.04; HR 1.57, 95% CI, 1.17, 2.10; respectively). Kaplan–Meier analysis showed that low HRR was associated with shortened OS. The relationship between HRR and the risk of death was consistent across all patient subgroups after stratification by subgroup analysis. Conclusions: These findings showed that a lower pretreatment HRR could be a potentially valuable prognostic factor in patients with advanced NSCLC.